Social comparison during political transition: Interaction of entity versus incremental beliefs and social Identities - HONG, Ying-Yi (Institutional Knowledge at Singapore Management University, 1999)
The relation between intergroup perceptions and peoples implicit theories of the malleability of human attributes or character was examined. We predicted that people who believe that human attributes are fixed (entity theorists) may also view a group as an entity and thus would rely on trait-based dimensions in social comparison to achieve group distinctiveness. By contrast, people who believe that human attributes are malleable (incremental theorists) may focus on the dynamic aspects of social groups (e.g., group goals) and thus would be less likely to rely on trait-based dimensions in social comparison. Moreover, such differential tendency was expected to become more salient as the day of the handover approached. These predictions were tested in a longitudinal study conducted in Hong Kong during the 1997 political transition. Implicit theories, social identities and group categorization strategies of 242 university students were assessed first in March, 1996, and then in September, 1996 and March, 1997. The findings supported our predictions and were discussed in terms of their implications for intergroup relations.